The efforts to improve learning result in integrated IPS with cooperative models of NHT types - Sari, Monika; Rambe, Yasir Maulana; Srizkiani, Erin (Universitas Riau Kepulauan, 2023)
Education is essentially a process of change for the better. The change process does not always go well. In learning practice, problems are often encountered related to not achieving the expected changes. Learning outcomes represent changes in the overall learning process that has been carried out previously. The problem that often occurs is low student learning outcomes. This research was conducted to improve student learning outcomes by implementing the Numbered Heads Together (NHT) Cooperative Model in social studies learning. This research uses an action study (action research) on class VII students of SMP IT Ar-Rislah Batam in two cycles. Research data was obtained through the distribution of test instruments, observation and documentation. After the information was obtained, the results were reviewed through descriptive statistical analysis. The research results show that the application of the Numbered Head Together (NHT) cooperative model in social studies learning makes it easier for teachers to achieve learning goals and is able to maximize student learning outcomes. The average value of learning outcomes obtained by students experienced a positive increase. In the pre-cycle stage it was 71.6, in the first cycle it was 80, and in the second cycle it rose to 88. So, the target set at ≥ 90% for the standard of completeness of classical student learning outcomes and ≥ 75 average scores for individuals has been achieved.